Evaluation of Titer E-Z Vaccine in Six-month Old Infants - Sirikwin, Siriwan; Lohlaka, Somsak; Waradagwinyoo, Simakant (Journal of Health Science of Thailand, 1994)
This study was performed at well baby clinic at Bamrasnaradura Hospital between March 1, 1992 - May 30, 1992. There were 47 infants enrolled in the study. Each infant was determined HI antibody before receiving 0.5 ml. of high titer Edsmonton Zagreb measles vaccine [100,000 TICD50] subcutaneously. HI antibody was repeatedly determined at 8 months of age. In conclusion, such vaccine was safe and effective, it produced higher HI antibody and higher seroconversion rate.